Nanopesticides in Agriculture: Benefits and Challenge in Agricultural Productivity, Toxicological Risks to Human Health and Environment - Marco Chaud; Eliana B. Souto; Aleksandra Zielinska; Patricia Severino; Fernando Batain; Jose Oliveira-Junior; Thais Alves (Toxics, 2021)
Nanopesticides are nanostructures with two to three dimensions between 1 to 200 nm, used to carry agrochemical ingredients (AcI). Because of their unique properties, the loading of AcI into nanoparticles offers benefits when compared to free pesticides. However, with the fast development of new engineered nanoparticles for pests’ control, a new type of environmental waste is being produced. This paper describes the nanopesticides sources, the harmful environmental and health effects arising from pesticide exposure. The potential ameliorative impact of nanoparticles on agricultural productivity and ecosystem challenges are extensively discussed. Strategies for controlled release and stimuli-responsive systems for slow, sustained, and targeted AcI and genetic material delivery are reported. Special attention to different nanoparticles source, the environmental behavior of nanopesticides in the crop setting, and the most recent advancements and nanopesticides representative research from experimental results are revised. This review also addresses some issues and concerns in developing, formulating and toxicity pesticide products for environmentally friendly and sustainable agriculture.